Alkaloids from Stems of Esenbeckia leiocarpa Engl. (Rutaceae) as Potential Treatment for Alzheimer Disease - Cardoso-Lopes, Elaine Monteiro; Maier, James Andreas; da Silva, Marcelo Rogerio; Ragasini, Luis Octavio [UNESP]; Simote, Simone Yasue [UNESP]; Lopes, Norberto Peporine; Pirani, Jose Rubens; Bolzani, Vanderlan da Silva [UNESP]; Marx Young, Maria Claudia (Mdpi Ag, 2010)
Esenbeckia leiocarpa Engl. (Rutaceae), popularly known as guaranta, goiabeira, is a native tree from Brazil. Bioactivity-guided fractionation of the ethanol stems extract afforded the isolation of six alkaloids: leiokinine A, leptomerine, kokusaginine, skimmianine, maculine and flindersiamine. All isolated compounds were tested for acetyl cholinesterase inhibition, in vitro and displayed anticholinesterasic activity. The alkaloid leptomerine showed the highest activity (IC(50) = 2.5 mu M), similar to that of the reference compound galanthamine (IC(50) = 1.7 mu M). The results showed for the first time the presence of alkaloids leptomerine and skimmianine in E. leiocarpa (Engl.) with potent anticholinesterasic activity.
Keywords: Esenbeckia leiocarpa; Rutaceae; alkaloids; acetylcholinesterase inhibitors